OPTIMASI PARAMETER EKSTRAKSI OLEORESIN DARI AMPAS PALA MENGGUNAKAN RESPONSE SURFACE METHODOLOGY (Optimization of Extraction Parameter of Oleoresin from Nutmeg Waste through Response Surface Methodology) - Darmadi, Darmadi; Riza, Medyan; Lubis, Mirna Rahmah (Baristand Industri Banda Aceh, 2015)
Optimization of extraction parameter of oleoresin from nutmeg waste has been developed.The waste could be alternative raw material of oleoresin to replace fresh nutmeg whose price is costly. Sofar, nutmeg waste from volatile oil factory is not utilized maximally. Its utilization as product that hasadditional value could be carried out by extraction method of nutmeg oleoresin. The research aims tooptimize oleoresin extraction condition (temperature, solvent amount, and particle size) from nutmegwaste by using Response Surface Methodology. The condition is designed randomly by Box-Behnkenmethod to result in 17 experiment. The effect of extraction condition toward yield and index of refractionis determined through calculation and analysis by using refractometer, respectively. The highest value ofindex of refraction in the research is 1.4852. The optimum condition to result in the highest yield14.5525% is at temperature of 40oC, solvent amount of 200 ml, and particle size of -20+30 mesh.Optimization by using the method indicates that optimum parameter is obtained at temperature of35.86oC, solvent amount of 167.13 ml, and particle size of 10 mesh. The research result is expected toprovide information on operational effectivity in the perspective of production cost that could be utilizedby production center of nutmeg oleoresin.